(3GdTQcI GdeJYOOI GdLfSjI (B:s (3BdjI GdJchjf hGSGdjH GdfTGW (B/s - (3OQjO, eMehO Ydjs ((3HjQhJ(B: s (3efThQGJ GdMdHj GdMbhbjI(B, s, 2009)
(3Gdeaghe GdbGfhfj ddTQcI GdeJYOOI GdLfSjI , fTCI GdTQcGJ GdeJYOOI GdLfSjI h JWhQgG , GdTcd GdbGfhfj ddTQcI GdeJYOOI GdLfSjI , GdTQcI GdhdjOI HhUagG YGedG ef YhGed bjGe GdTQcI GdeJYOOI GdLfSjI , GdYdGbI GdbGfhfjI Hjf GdTQcI GdCe h GdTQcGJ GdhdjOI , NUhUjI eaghe GdTNUjI GdbGfhfjI ddTQcI GdeJYOOI GdLfSjI , fJGFL GcJSGH GdTQcI GdeJYOOI GdLfSjI ddTNUjI GdbGfhfjI , WHjYI GdTNUjI GdbGfhfjI ddTQcI GdhdjOI , GdGOGQI GdeQcRjI aj GdTQcI GdeJYOOI GdLfSjI , CSGdjH SjWQI GdGOGQI GdeQcRjI Ydi EOGQGJ GdTQcGJ GdhdjOI , Gdeaghe GdbGfhfj ddGSJKeGQ GdOhdj , GdGSJKeGQ GdOhdj ddTQcI GdeGYOOI GdLfSjI ef MjK Tcdg h VeGfGJg , OhQ GdGSJKeGQ GdOhdj aj fbd GdJcfhdhLjG , GdQbGHI GdOGNdjI h GdQbGHI GdNGQLjI Ydi GdTQcI GdeJYOOI GdLfSjI , JbOjQ GdQbGHI GdbGfhfjI Ydi GdTQcGJ GdeJYOOI GdLfSjI , GdGTcGdjGJ GdbGfhfjI Hjf GdOhdI GdeVjaI h GdTQcI GdeJYOOI GdLfSjI , GdhSGFd GdbGfhfjI dJShjI GdefGRYGJ Hjf GdTQcI GdeJYOOI GdLfSjI h GdOhdI GdeVjaI , GdJfXje GdbGfhfj GdOhdj ddTQcGJ GdeJYOOI GdLfSjI (B.s
(3eQGLY U(B.347s
Keywords: (3GdTQcGJs; (3GdTQcGJ eJYOOI GdLfSjIs